Study on The Influence of Typhoon on Coastal Bridges and Countermeasures - Zhu, Baoni (Transactions on Engineering and Technology Research, 2024)
As an important medium connecting land and promoting traffic, the safety of coastal bridge should also be paid attention to. Typhoon as a natural disaster will cause direct and indirect damage to the bridge. This paper studies the influence of typhoon on coastal bridge and its countermeasures. Firstly, the direct damage to bridge structure caused by typhoon wind load and wind direction changes and the indirect damage caused by typhoon erosion, sand damage and concrete carbonation are analyzed. Then, the design scheme and bridge management scheme are proposed to reduce the harm caused by typhoon. Finally, taking Sutong Bridge as an example, the wind resistance design of the bridge is discussed, and the function of the bridge health monitoring system in the operation stage is introduced, which provides important data support for the safety assessment and maintenance of the bridge structure. The results show that the negative impact of typhoon on coastal bridge can be reduced by bridge health management. The research can provide feasible solutions for Bridges to cope with typhoons in the future.